Efektivitas Evaluasi Proses Model Pembelajaran Berbasis Masalah Materi Qurban dan Aqiqah - Dzulkifli, Muhamad Arham; Kamil, Muhammad Ihsan; Rizal, Muhammad; Ramdhani, Muhammad Ali; Rochman, Chaerul (Universitas Islam Sultan Agung, 2022)
In essence, learning is a psychological process or personal event that occurs within each individual. Learning is not an automatic consequence of contemplating information into students' minds, learning requires mental involvement and students' own work. Explanation and demonstration alone will not produce good learning outcomes, but a learning experience that is more related to conceptual elements will make the learning process more effective. One alternative that can be applied in PAI learning is learning activities by applying a problem-based learning model that aims to improve student achievement and motivation in understanding and mastering PAI lessons. This study aims to examine the effectiveness of the problem-based learning model in Islamic religious education lessons on qurban and akikah material. This study uses a quantitative approach, which uses scores to describe the variables of student learning outcomes and the effectiveness of learning implementation. The population in this study were 29 students with 14 female groups and 15 male groups in class IX SMPN 54 Bandung. The data obtained were in the form of answers based on the evaluation of the learning process, namely 13 questions that were answered authentically. The data obtained were then analyzed descriptively. Data was collected using the method. Student learning outcomes showed an average above the KKM (â‰¥80) which was 84%. So that the achievement of the effectiveness of the evaluation of problem-based learning in the qurban and akikah material for the female group was greater, namely 86% compared to the male group, which was lower at 83%.